Composite catalyst for preparing low-carbon olefin through hydrogenation as well as preparation method and application of composite catalyst

By using a composite catalyst of molecular sieve such as FeCu/TiO2 and SAPO-34, the problems of low selectivity and conversion of hydrogenated low-carbon olefin catalysts in the prior art are solved, and efficient CO2 resource utilization and catalyst life are achieved.

CN119793525APending Publication Date: 2025-04-11HUANENG CLEAN ENERGY RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411941750.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, the hydrogenated low-carbon olefin catalyst has a low selectivity and conversion rate in the reaction to convert CO2 into low-carbon olefins, and the catalyst life is short, making it difficult to achieve efficient CO2 resource utilization.

Method used

FeCu/TiO2 is used as the first component and combined with SAPO-34, SAPO-18, ZSM-5 or SSZ-13 molecular sieve as the composite catalyst of the second component, the catalyst is prepared by co-precipitation and mechanical mixing, and the component ratio and particle size distribution are optimized to improve the activity and selectivity of the catalyst.

Benefits of technology

It significantly improves the CO2 conversion rate and the selectivity of low-carbon olefins, extends the service life of the catalyst, achieves more efficient CO2 resource utilization, and promotes the green transformation and economic sustainable development of the chemical industry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005212683450000121
    Figure BDA0005212683450000121
  • Figure BDA0005212683450000122
    Figure BDA0005212683450000122
  • Figure BDA0005212683450000123
    Figure BDA0005212683450000123
Patent Text Reader

Abstract

The invention provides a low-carbon olefin composite catalyst prepared through hydrogenation and a preparation method and application thereof.The catalyst comprises a first component and a second component, the first component is FeCu / TiO2, the second component is at least one of SAPO-34 molecular sieves, SAPO-18 molecular sieves, ZSM-5 molecular sieves and SSZ-13 molecular sieves, Fe in the first component is ferric oxide, and Cu in the first component is copper oxide. Under the synergistic effect of the two types of metal matrixes and TiO2 in the first component and the synergistic effect of the first component and the second component, the selectivity and conversion rate of the catalyst for preparing low-carbon olefin from CO2 can be effectively improved, and the catalyst can also have a relatively long service life. Particularly, TiO2 in the first component can be used as a metal-based carrier, provides more oxygen vacancies for the catalyst, and can further improve the conversion rate and selectivity of the reaction for preparing low-carbon olefin through hydrogenation by utilizing the adsorption effect of TiO2 on the raw material H2.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of chemical energy, and in particular to a composite catalyst for preparing low-carbon olefins by hydrogenation, and a preparation method and application thereof. Background Art

[0002] Climate change is one of the most serious challenges facing the world today, and it is directly related to the sustainable development of human society and ecological balance. With the rapid development of industrialization, carbon emissions have shown a significant upward trend, causing unprecedented pressure on the environment.

[0003] As a major greenhouse gas, CO2's effective utilization technology is becoming an innovative solution to transform CO2 from an environmental burden to an economic resource. By converting CO2 into higher-value chemicals, such as low-carbon olefins (ethylene, propylene, etc.), sustainable income can be created to offset the high cost of carbon capture and storage technology, achieve the economic feasibility of CO2 emission reduction, and gradually transition from high-cost emission reduction to low-cost or even negative-cost emission reduction.

[0004] Low-carbon olefins such as ethylene and propylene are important basic raw materials and platform compounds, and are one of the world's largest chemical products. Ethylene and propylene are the core of the petrochemical industry and occupy an important position in the national economy. However, the production of low-carbon olefins consumes a large amount of fossil energy and generates hundreds of millions of tons of carbon emissions each year. If renewable energy and CO2 are used as the source, the hydrogen produced by renewable energy power generation (called green hydrogen) is reacted with CO2 to convert it into low-carbon olefins, and then synthesized into plastics, rubber, fibers and other materials, it is possible to fix carbon in materials for long-term use and achieve near-zero CO2 emissions from the entire process from production to use.

[0005] There are usually two reaction pathways for CO2 hydrogenation to olefins. The first is the Fischer-Tropsch synthesis pathway, where iron, cobalt and other Fischer-Tropsch synthesis catalysts first convert CO2 into CO through the reverse water-gas shift reaction, and then convert CO and H2 into hydrocarbons. Due to the distribution restrictions of ASF, the product distribution in this process is relatively wide, and the selectivity of low-carbon olefins is usually less than 60%. The second is to use methanol as an intermediate, convert CO2 into methanol through metal oxides, and then dehydrate methanol into low-carbon olefins through molecular sieves. Since metal-based catalysts have weak adsorption and activation capabilities for CO2, the CO2 single-pass conversion rate of metal-based catalysts is low.

[0006] In summary, the technical problem that needs to be solved urgently is to improve the selectivity, conversion rate and catalyst life of the CO2 to light olefins catalyst, so as to achieve more efficient CO2 resource utilization and promote the green transformation and economic sustainable development of the chemical industry. Therefore, the present invention is proposed. Summary of the invention

[0007] The main purpose of the present invention is to provide a composite catalyst for hydrogenating light olefins and a preparation method and application thereof, so as to solve the problems in the prior art that when the hydrogenating light olefins catalyst uses CO2 as a raw material to prepare light olefins, the catalyst cannot have a high conversion rate and a high selectivity for light olefins in the hydrogenating light olefins reaction, and the existing hydrogenating light olefins catalyst has a short service life.

[0008] In order to solve the above problems, the present invention provides a composite catalyst for hydrogenating light olefins, which comprises a first component and a second component, wherein the first component is FeCu / TiO2, the second component is at least one of SAPO-34 molecular sieve, SAPO-18 molecular sieve, ZSM-5 molecular sieve and SSZ-13 molecular sieve, and the Fe in the first component is iron oxide, and the Cu in the first component is copper oxide.

[0009] Furthermore, the weight ratio of the first component to the second component is (1-5):1; preferably, the molar ratio of Fe and Cu in the first component is (0.5-2):1, and the ratio of the molar number of TiO2 to the total molar number of Fe and Cu is (0.01-0.25):1; further preferably, the molar ratio of Fe and Cu in the first component is (0.8-1.5):1, and the ratio of the molar number of TiO2 to the total molar number of Fe and Cu is (0.10-0.20):1; preferably, the second component is SAPO-34 molecular sieve; preferably, the particle size of the composite catalyst for hydrogenation to produce light olefins is 10-100 mesh.

[0010] According to another aspect of the present invention, a method for preparing the above-mentioned composite catalyst for hydrogenating low-carbon olefins is also provided, and the preparation method comprises the following steps: dissolving a soluble salt of Fe and a soluble salt of Cu in water to obtain a mixed solution, heating the mixed solution and sequentially adding TiO2 and a precipitant thereto to carry out a co-precipitation reaction to obtain a mixed slurry; separating the mixed slurry, drying and calcining the obtained solid matter to obtain an active precursor FeCu / TiO2; mixing the active precursor FeCu / TiO2 and a second component to obtain a composite catalyst for hydrogenating low-carbon olefins.

[0011] Further, when the pH of the coprecipitation reaction system is 6 to 9, the addition of the precipitant is stopped; preferably, when the pH of the coprecipitation reaction system is 6 to 8, the addition of the precipitant is stopped; preferably, the precipitant is an aqueous carbonate solution; preferably, the aqueous carbonate solution is at least one of an aqueous sodium carbonate solution, an aqueous potassium carbonate solution and an ammonium carbonate solution; preferably, the concentration of the precipitant is 0.1 to 1 mol / L; preferably, the concentration of the soluble salt of Fe in the mixed solution is 0.1 to 1.0 mol / L; preferably, the concentration of the soluble salt of Cu in the mixed solution is 0.1 to 0.8 mol / L.

[0012] Furthermore, the temperature of the coprecipitation reaction is 30-90°C; preferably, the coprecipitation reaction time is 1-12h; preferably, after the coprecipitation reaction is completed, it is allowed to stand and age to obtain a mixed slurry; preferably, the standing and aging time is 0.1-8h.

[0013] Furthermore, the drying temperature is 100-120°C, and the drying time is 2-24h; preferably, the calcination temperature is 300-600°C, and the calcination time is 2-6h; preferably, the particle size of the active precursor FeCu / TiO2 is 10-100 mesh; preferably, the particle size of the second component is 20-100 mesh; preferably, the particle size of TiO2 is 10-100nm.

[0014] According to the third aspect of the present invention, there is also provided a hydrogenation reaction for producing light olefins, wherein the hydrogenation reaction for producing light olefins uses CO2 as a raw material and the above-mentioned hydrogenation reaction for producing light olefins composite catalyst as a catalyst.

[0015] According to the fourth aspect of the present invention, a method for hydrogenating to produce light olefins is also provided, the method comprising: subjecting a hydrogenating to produce light olefins composite catalyst to reduction pretreatment in the presence of a reducing gas to obtain an active hydrogenating to produce light olefins composite catalyst; subjecting H2 gas and CO2 gas to a hydrogenating to produce light olefins reaction under the action of the active hydrogenating to produce light olefins composite catalyst.

[0016] Furthermore, the reducing gas comprises a mixture of a first gas and a second gas, wherein the first gas is hydrogen, and the second gas is at least one of nitrogen, argon and helium; preferably, the space velocity of the mixture of the first gas and the second gas is 1000 to 20000 mL / (gcat·h); preferably, the reduction temperature is 200 to 400° C., the reduction time is 2 to 5 h, and the reduction pressure is 0.09 to 0.11 MPa; preferably, the volume ratio of the first gas to the second gas in the mixture is (0.05 to 19):1.

[0017] Furthermore, the volume ratio of H2 gas and CO2 gas is (2-4):1; preferably, the space velocity of the hydrogenation reaction of H2 gas and CO2 gas to produce light olefins is 1000-20000 mL / (gcat·h); preferably, the temperature of the hydrogenation reaction to produce light olefins is 300-400°C, and the reaction pressure is 1-4 MPa; preferably, the mixture of H2 gas and CO2 gas also includes 1-10% by volume of at least one of nitrogen, argon and helium as a protective gas.

[0018] The present invention provides a composite catalyst for preparing low-carbon olefins by hydrogenation, and a preparation method and application thereof. The composite catalyst for preparing low-carbon olefins by hydrogenation comprises a first component and a second component, wherein the first component is FeCu / TiO2, the second component is at least one of SAPO-34 molecular sieve, SAPO-18 molecular sieve, ZSM-5 molecular sieve and SSZ-13 molecular sieve, and the Fe in the first component is iron oxide, and the Cu in the first component is copper oxide. The first component in the composite catalyst for preparing low-carbon olefins by hydrogenation comprises two types of metal-based forms, and a highly efficient multi-active site is constructed; in addition, the TiO2 in the first component, as a carrier of two metal-based forms, can not only provide a certain mechanical strength for the composite catalyst, but also can further improve the adsorption effect of the catalyst on the reaction process of preparing low-carbon olefins by hydrogenation and the raw material H2 and provide more oxygen vacancies, increase the contact area between the reaction CO2 and H2, and under the adsorption effect of TiO2 on the raw material H2, the catalytic effect of the first stage can be completed more effectively, so that the raw material CO2 can be better converted into intermediate methanol and low-carbon olefin products, and the catalytic activity of the catalyst is effectively improved. Furthermore, under the action of a second component including at least one of SAPO-34 molecular sieve, SAPO-18 molecular sieve, ZSM-5 molecular sieve and SSZ-13 molecular sieve, the methanol produced in the first stage catalytic process can be further converted into light olefins, and the long-chain hydrocarbons produced in the first stage catalytic process can be further broken to generate light olefins. The dual action of the second component can further improve the selectivity of light olefins.

[0019] In summary, the composite catalyst for preparing low-carbon olefins by hydrogenation proposed by the present invention can effectively improve the conversion rate of the catalyst for preparing low-carbon olefins by CO2 and the selectivity for low-carbon olefins under the synergistic effect of the two types of metal bases and TiO2 in the first component, and under the synergistic effect of the first component and the second component, and can also make the obtained catalyst have a longer service life. The composite catalyst for preparing low-carbon olefins by hydrogenation is of great significance for achieving more efficient CO2 resource utilization and promoting the green transformation of the chemical industry and sustainable economic development. DETAILED DESCRIPTION

[0020] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0021] As described in the background technology section, in the prior art, the Fischer-Tropsch synthesis pathway based on catalysts such as iron and cobalt first converts CO2 into CO, and then reacts with hydrogen to generate hydrocarbons. However, due to the distribution of the product being limited by the Andresen-Fox-Freininghausen distribution (ASF distribution), the selectivity of low-carbon olefins is usually less than 60%, and the product distribution is wide, which is not conducive to the efficient production of the target product. Based on methanol as an intermediate, CO2 is converted into methanol by metal oxides, and then methanol is converted into low-carbon olefins by molecular sieves (such as SAPO-34), but due to the weak adsorption activation ability of metal-based catalysts for CO2, the single-pass conversion rate of CO2 is low. The above limitations, coupled with the problem of short catalyst life, have become key technical bottlenecks that restrict the efficient conversion of CO2 into low-carbon olefins. How to improve the selectivity, conversion rate and catalyst life of CO2 catalysts for low-carbon olefins to achieve more efficient CO2 resource utilization and promote the green transformation and economic sustainable development of the chemical industry is a problem that needs to be solved urgently.

[0022] In order to solve the above problems, the present invention provides a composite catalyst for hydrogenating light olefins, which comprises a first component and a second component, wherein the first component is FeCu / TiO2, the second component is at least one of SAPO-34 molecular sieve, SAPO-18 molecular sieve, ZSM-5 molecular sieve and SSZ-13 molecular sieve, and the Fe in the first component is iron oxide, and the Cu in the first component is copper oxide.

[0023] The composite catalyst for preparing low-carbon olefins by hydrogenation provided by the present invention comprises a first component and a second component, wherein the first component is FeCu / TiO2, the Fe-based part in the first component can not only serve the purpose of converting the raw material CO2 into CO, but also can further convert the generated CO into a variety of products including low-carbon olefins, while the Cu-based part in the first component can serve the purpose of converting CO into methanol. The composite catalyst for preparing low-carbon olefins by hydrogenation comprises the above two types of metal-based forms, constructs an efficient multi-active site, and under the synergistic effect of the above two metal-based catalysts, can more effectively complete the catalytic effect of the first stage, so that the raw material CO2 can be better converted to intermediate methanol and low-carbon olefin products, can effectively improve the catalytic activity of the catalyst, and improve the conversion rate of raw material CO2. In addition, the inventors have found through a large number of experiments that the composite of two metal oxides, iron oxide and copper oxide, can also effectively improve the activity and selectivity of the composite catalyst for preparing low-carbon olefins by hydrogenation, breaking the restrictive problem between activity and selectivity in traditional catalysts, and further improving the catalytic selectivity and life of the composite catalyst for preparing low-carbon olefins by hydrogenation. Furthermore, under the action of a second component including at least one of SAPO-34 molecular sieve, SAPO-18 molecular sieve, ZSM-5 molecular sieve and SSZ-13 molecular sieve, the methanol produced in the first stage catalytic process can be further converted into light olefins, and the long-chain hydrocarbons produced in the first stage catalytic process can be further broken to generate light olefins. The dual action of the second component can further improve the selectivity of light olefins.

[0024] In particular, the first component FeCu / TiO2 in the hydrogenation light olefin composite catalyst provided by the present invention also includes TiO2. First, TiO2, as a carrier of two metal bases, can provide a certain mechanical strength for the hydrogenation light olefin composite catalyst; second, TiO2, because it has a large number of oxygen vacancies, can make the oxygen atoms in the adsorbed CO2 embedded therein, and then the two metal active components of iron oxide and copper oxide synergistically catalyze it further, thereby breaking the carbon oxygen bond, realizing the activation of CO2, which is conducive to further improving the overall conversion rate of the reaction; third, TiO2 can also further improve the adsorption effect of the catalyst on the hydrogenation light olefin reaction process and the raw material H2, increase the contact area between the reaction raw material and the raw material, and under the adsorption effect of TiO2 on the raw material H2, the CO produced in the first stage can be more fully contacted with H2, thereby improving the reaction conversion rate and selectivity. Under the coordinated effect of the above-mentioned multiple effects, the conversion rate of the hydrogenation light olefin composite catalyst for CO2 and the selectivity for light olefins in the hydrogenation light olefin reaction process can be further improved.

[0025] In summary, the composite catalyst for preparing low-carbon olefins by hydrogenation provided by the present invention can effectively improve the selectivity and conversion rate of the catalyst for preparing low-carbon olefins by CO2 under the synergistic effect of the two types of metal bases and TiO2 in the first component, and under the synergistic effect of the first component and the second component, and can also make the obtained catalyst have a longer service life. The composite catalyst for preparing low-carbon olefins by hydrogenation is useful for achieving more efficient resource utilization of CO2.

[0026] It should be further explained here that SAPO-34 molecular sieve, SAPO-18 molecular sieve, ZSM-5 molecular sieve and SSZ-13 molecular sieve are all known materials in the prior art.

[0027] In a preferred embodiment, the weight ratio of the first component to the second component is (1-5):1; preferably, the molar ratio of Fe and Cu in the first component is (0.5-2):1, and the ratio of the molar number of TiO2 to the total molar number of Fe and Cu is (0.01-0.25):1. Controlling the weight ratio of the first component to the second component in the hydrogenation catalyst for light olefins and controlling the relative proportion of Fe, Cu and TiO2 in the first component within the above range can better play the system effect of the above components and further improve the selectivity and catalytic activity of the catalyst. Further preferably, the molar ratio of Fe and Cu in the first component is (0.8-1.5):1, and the ratio of the molar number of TiO2 to the total molar number of Fe and Cu is (0.10-0.20):1; the relative proportion of Fe, Cu and TiO2 in the first component of the hydrogenation catalyst for light olefins is within the above preferred range, and the catalytic activity and selectivity of the catalyst are better. Preferably, the second component is SAPO-34 molecular sieve; SAPO-34 molecular sieve in the above catalyst can better convert the methanol produced in the first stage catalytic process into light olefins and further break the long chain hydrocarbons produced in the first stage catalytic process to generate light olefins, which is conducive to further improving the selectivity for light olefins. Preferably, the particle size of the hydrogenation light olefin composite catalyst is 10 to 100 meshes.

[0028] According to another aspect of the present invention, a method for preparing the above-mentioned composite catalyst for hydrogenating low-carbon olefins is also provided, and the preparation method comprises the following steps: dissolving a soluble salt of Fe and a soluble salt of Cu in water to obtain a mixed solution, heating the mixed solution and sequentially adding TiO2 and a precipitant thereto to carry out a co-precipitation reaction to obtain a mixed slurry; separating the mixed slurry, drying and calcining the obtained solid matter to obtain an active precursor FeCu / TiO2; mixing the active precursor FeCu / TiO2 and a second component to obtain a composite catalyst for hydrogenating low-carbon olefins.

[0029] Specifically, in the above preparation method, the soluble salt of Fe and the soluble salt of Cu are first dissolved in water to obtain a mixed solution, and then TiO2 is first added to the mixed solution during heating to form a suspension, and then a precipitant is added thereto to perform a coprecipitation reaction to obtain a mixed slurry; after the obtained mixed slurry is separated into solid and liquid, the obtained solid material is dried and calcined to obtain an active precursor FeCu / TiO2; after the active precursor FeCu / TiO2 and the second component are mechanically mixed, a composite catalyst for hydrogenation to produce low-carbon olefins can be obtained. By way of example but not limitation, the soluble salt of Fe is ferric nitrate, and the soluble salt of Cu is copper nitrate.

[0030] In a preferred embodiment, when the pH of the coprecipitation reaction system is 6 to 9, the addition of the precipitant is stopped; by controlling the pH of the coprecipitation reaction system within the above range, the solid component in the prepared mixed slurry can have a smaller particle size, which is conducive to better mixing and loading of FeCu and TiO2 in the first component, and further improving the catalytic performance of the catalyst. Preferably, when the pH of the coprecipitation reaction system is 6 to 8, the addition of the precipitant is stopped; by controlling the pH of the coprecipitation reaction system within the preferred range, the above effect is better. Preferably, the precipitant is a carbonate aqueous solution; preferably, the carbonate aqueous solution is at least one of a sodium carbonate aqueous solution, a potassium carbonate aqueous solution and an ammonium carbonate aqueous solution; preferably, the concentration of the precipitant is 0.1 to 1 mol / L; by using the above precipitant and controlling the concentration of the precipitant within the above range, the coprecipitation reaction can be performed better. Preferably, the concentration of the soluble salt of Fe in the mixed solution is 0.1 to 1.0 mol / L; preferably, the concentration of the soluble salt of Cu in the mixed solution is 0.1 to 0.8 mol / L. By controlling the concentration of soluble salts of Fe and Cu in the mixed solution, Fe and Cu can be better loaded on the surface of TiO2, and the coprecipitation reaction rate can be controlled within a more appropriate range, further improving the catalytic activity and catalytic selectivity of the composite catalyst for hydrogenation to produce light olefins.

[0031] In a preferred embodiment, the temperature of the coprecipitation reaction is 30 to 90°C; preferably, the time of the coprecipitation reaction is 1 to 12 hours; the temperature in the coprecipitation reaction will affect the particle size and load uniformity of the active precursor FeCu / TiO2. Controlling the temperature and time of the coprecipitation reaction within the above range can make the catalytic activity and catalytic selectivity of the obtained active precursor FeCu / TiO2 and the catalyst better. Preferably, after the coprecipitation reaction is completed, it is subjected to static aging to obtain a mixed slurry; preferably, the static aging time is 0.1 to 8 hours. After the coprecipitation reaction is completed, static aging can further improve the above effect.

[0032] In a preferred embodiment, the drying temperature is 100-120°C and the drying time is 2-24h; preferably, the calcination temperature is 300-600°C and the calcination time is 2-6h; preferably, the particle size of the active precursor FeCu / TiO2 is 10-100 mesh; preferably, the particle size of the second component is 20-100 mesh. Controlling the temperature and time of drying and calcination, as well as the particle size of the active precursor and the second component within the above range, can make the prepared hydrogenation to light olefin composite catalyst have better overall effect. Preferably, the particle size of TiO2 is 10-100nm. Preferably, the particle size of the active precursor FeCu / TiO2 is 10-100 mesh. Controlling the particle size of the active precursor FeCu / TiO2 within the above range can make the obtained hydrogenation to light olefin composite catalyst have better mechanical strength. Preferably, before the active precursor FeCu / TiO2 is mixed with the second component, the active precursor is compacted and crushed to obtain the active precursor FeCu / TiO2 with a particle size of 10 to 100 meshes. The above tableting and crushing operations are because the particle size of the active precursor FeCu / TiO2 after coprecipitation reaction and drying and sintering is very small. After tableting, the TiO2 matrix and the active metal component in the active precursor can be more closely combined; after crushing, it can be better mixed with the second component, which is conducive to further improving the catalytic performance of the catalyst.

[0033] According to the third aspect of the present invention, an application of the above-mentioned composite catalyst for hydrogenating to prepare light olefins is also provided. Using CO2 as a raw material and the above-mentioned composite catalyst for hydrogenating to prepare light olefins as a catalyst, a hydrogenation to prepare light olefins reaction is carried out. The composite catalyst for hydrogenating to prepare light olefins of the present invention is used for the hydrogenation to prepare light olefins reaction, which can effectively improve the conversion rate of CO2 in the hydrogenation to prepare light olefins reaction and the selectivity for light olefins.

[0034] According to the fourth aspect of the present invention, a method for hydrogenation to produce light olefins is also provided, the method comprising: subjecting a hydrogenation to produce light olefins composite catalyst to reduction pretreatment in the presence of a reducing gas to obtain an active hydrogenation to produce light olefins composite catalyst; subjecting H2 gas and CO2 gas to a hydrogenation to produce light olefins reaction under the action of the active hydrogenation to produce light olefins composite catalyst. In the above method, the obtained hydrogenation to produce light olefins composite catalyst is first subjected to reduction pretreatment in a reducing gas atmosphere to obtain an active hydrogenation to produce light olefins composite catalyst; and the obtained active hydrogenation to produce light olefins composite catalyst is then used for a hydrogenation to produce light olefins reaction using H2 gas and CO2 gas as raw materials.

[0035] In a preferred embodiment, the reducing gas comprises a mixed gas composed of a first gas and a second gas, wherein the first gas is hydrogen, and the second gas is at least one of nitrogen, argon and helium; preferably, the space velocity of the mixed gas composed of the first gas and the second gas is 1000-20000 mL / (gcat·h); preferably, the reduction temperature is 200-400°C, the reduction time is 2-5h, and the reduction pressure is 0.09-0.11 MPa; preferably, the volume ratio of the first gas to the second gas in the mixed gas is (0.05-19): 1. Controlling the parameters of the reduction pretreatment process of the hydrogenation to prepare light olefins composite catalyst within the above range can fully activate the hydrogenation to prepare light olefins composite catalyst and better exert its catalytic performance and selectivity.

[0036] In a preferred embodiment, the volume ratio of H2 gas and CO2 gas is (2-4):1; preferably, the space velocity of the hydrogenation reaction of H2 gas and CO2 gas to produce light olefins is 1000-20000mL / (gcat·h); preferably, the temperature of the hydrogenation reaction to produce light olefins is 300-400°C, and the reaction pressure is 1-4MPa. Controlling the parameters in the hydrogenation reaction process to produce light olefins within the above range can further improve the selectivity and yield of the reaction. Preferably, the H2 gas and CO2 gas mixture also includes 1-10% volume of at least one of nitrogen, argon and helium as a protective gas. Mixing the H2 gas and CO2 gas mixture into the protective gas can further improve the safety of the reaction process. Further preferably, the space velocity of the hydrogenation reaction of H2 gas and CO2 gas to produce light olefins is 1000-10000mL / (gcat·h).

[0037] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0038] Example 1

[0039] (1) Preparation of composite catalyst for hydrogenation to produce light olefins

[0040] Ferric nitrate and copper nitrate are dissolved in water to obtain a mixed solution (the concentration of ferric nitrate in the mixed solution is 0.35 mol / L, and the molar ratio of ferric nitrate to copper nitrate is 1.37:1), which is placed in a water bath heating device with ultrasonic function and heated to 70°C, TiO2 with a particle size of 10 nm is added thereto, and then 1 mol / L sodium carbonate aqueous solution is added thereto for coprecipitation reaction, until the pH of the coprecipitation reaction system is 7, the addition of the precipitant is stopped, and the uniformly mixed system is subjected to static aging to obtain a mixed slurry, wherein the coprecipitation reaction time is 5 hours and the static aging time is 6 hours. The mixed slurry is separated, and the obtained solid material is dried at 100°C for 24 hours, and then calcined at 400°C for 3 hours to obtain an active precursor FeCu / TiO2. The active precursor is compacted and crushed, and a 20-40 mesh portion is screened out, which is mechanically mixed with a 20-40 mesh SAPO-34 molecular sieve to obtain a composite catalyst for hydrogenation to produce low-carbon olefins. The molar ratio of Fe to Cu in the composite catalyst for hydrogenation to produce low-carbon olefins is 1.37:1, the ratio of the molar number of added TiO2 to the total molar number of Fe and Cu is 0.15:1. The weight ratio of the active precursor FeCu / TiO2 and SAPO-34 molecular sieve is 2:1.

[0041] (2) Preparation of light olefins

[0042] The above-obtained composite catalyst for preparing light olefins by hydrogenation is placed in a fixed bed reactor, and is subjected to reduction pretreatment in a reducing mixed gas atmosphere consisting of the first gas hydrogen and the second gas nitrogen to obtain an active composite catalyst for preparing light olefins by hydrogenation. The volume ratio of the first gas hydrogen to the second gas argon is 4:1, the reduction temperature is 300°C, the reduction pressure is 0.11MPa, the reduction time is 3h, and the space velocity of the reducing mixed gas consisting of the first gas hydrogen and the second gas argon is 6000mL / (gcat·h).

[0043] The H2 gas and CO2 gas are subjected to a hydrogenation reaction to produce light olefins under the action of an active hydrogenation catalyst. The volume ratio of the H2 gas and the CO2 gas is 3:1, and the mixture of the H2 gas and the CO2 gas also includes 4% nitrogen by volume. The space velocity of the hydrogenation reaction of the H2 gas and the CO2 gas to produce light olefins is 6000mL / (gcat·h). The temperature of the hydrogenation reaction to produce light olefins is 350°C, and the reaction pressure is 3MPa. The components of the product prepared above are tested, and the results are shown in Table 1.

[0044] Example 2

[0045] Ferric nitrate and copper nitrate are dissolved in water to obtain a mixed solution (the concentration of ferric nitrate in the mixed solution is 1.0 mol / L, and the molar ratio of ferric nitrate to copper nitrate is 1.37:1), which is placed in a water bath heating device with ultrasonic function and heated to 90°C, TiO2 with a particle size of 10 nm is added thereto, and then 1 mol / L potassium carbonate aqueous solution is added thereto for coprecipitation reaction, until the pH of the coprecipitation reaction system is 6, the addition of the precipitant is stopped, and the uniformly mixed system is subjected to static aging, and a coprecipitation reaction is carried out to obtain a mixed slurry, wherein the coprecipitation reaction time is 1h, and the static aging time is 0.1h. The mixed slurry is separated, and the obtained solid material is dried at 100°C for 24h, and then calcined at 300°C for 6h to obtain an active precursor FeCu / TiO2. The active precursor is compacted and crushed, and a 10-50 mesh portion is screened out, which is mechanically mixed with a 50-100 mesh SAPO-34 molecular sieve to obtain a composite catalyst for hydrogenation to produce low-carbon olefins. The molar ratio of Fe to Cu in the composite catalyst for hydrogenation to prepare low carbon olefins is 2:1, and the ratio of the molar number of added TiO2 to the total molar number of Fe and Cu is 0.01:1. The weight ratio of the active precursor FeCu / TiO2 and the SAPO-34 catalyst is 1:1, and the particle size is 10-100 meshes.

[0046] (2) Preparation of light olefins

[0047] The above-obtained composite catalyst for preparing light olefins by hydrogenation is placed in a fixed bed reactor, and is subjected to reduction pretreatment in a reducing mixed gas atmosphere consisting of the first gas hydrogen and the second gas nitrogen to obtain an active composite catalyst for preparing light olefins by hydrogenation. The volume ratio of the first gas hydrogen to the second gas nitrogen is 0.05:1, the reduction temperature is 400°C, the reduction pressure is 0.09MPa, the reduction time is 2h, and the space velocity of the reducing mixed gas consisting of the first gas hydrogen and the second gas nitrogen is 1000mL / (gcat·h).

[0048] The H2 gas and CO2 gas are subjected to a hydrogenation reaction to produce light olefins under the action of an active hydrogenation catalyst. The volume ratio of the H2 gas and the CO2 gas is 4:1, and the H2 gas and the CO2 gas mixture also includes 1% volume fraction of argon. The space velocity of the H2 gas and the CO2 gas for the hydrogenation reaction to produce light olefins is 10000 mL / (gcat·h). The temperature of the hydrogenation reaction to produce light olefins is 400°C, and the reaction pressure is 1MPa. The components of the product prepared above are tested, and the results are shown in Table 1.

[0049] Example 3

[0050] Ferric nitrate and copper nitrate are dissolved in water to obtain a mixed solution (the concentration of ferric nitrate in the mixed solution is 0.1 mol / L, and the molar ratio of ferric nitrate to copper nitrate is 1.37:1), which is placed in a water bath heating device with ultrasonic function and heated to 30°C, TiO2 with a particle size of 100 nm is added thereto, and then 0.1 mol / L ammonium carbonate aqueous solution is added thereto for coprecipitation reaction, until the pH of the coprecipitation reaction system is 9, the addition of the precipitant is stopped, and the uniformly mixed system is subjected to static aging, and a coprecipitation reaction is carried out to obtain a mixed slurry, wherein the coprecipitation reaction time is 12h and the static aging time is 8h. The mixed slurry is separated, and the obtained solid material is dried at 120°C for 2h, and then calcined at 600°C for 2h to obtain an active precursor FeCu / TiO2. The active precursor is compacted and crushed, and a 50-100 mesh portion is screened out, which is mechanically mixed with a 20-50 mesh SAPO-34 molecular sieve to obtain a composite catalyst for hydrogenation to produce low-carbon olefins. The molar ratio of Fe to Cu in the composite catalyst for hydrogenation to prepare low-carbon olefins is 0.5:1, and the ratio of the molar number of added TiO2 to the total molar number of Fe and Cu is 0.25:1. The weight ratio of the active precursor FeCu / TiO2 and SAPO-34 molecular sieve is 5:1, and the particle size is 20-100 mesh.

[0051] (2) Preparation of light olefins

[0052] The above-obtained composite catalyst for preparing light olefins by hydrogenation is placed in a fixed bed reactor, and is subjected to reduction pretreatment in a reducing mixed gas atmosphere consisting of hydrogen as the first gas and nitrogen as the second gas, to obtain an active composite catalyst for preparing light olefins by hydrogenation. The volume ratio of the first gas to the second gas is 19:1, the reduction temperature is 200°C, the reduction pressure is 0.11 MPa, the reduction time is 5 hours, and the space velocity of the reducing mixed gas consisting of the first gas and the second gas is 20000 mL / (gcat·h).

[0053] The H2 gas and CO2 gas are subjected to a hydrogenation reaction to produce light olefins under the action of an active hydrogenation catalyst. The volume ratio of the H2 gas and the CO2 gas is 2:1, and the H2 gas and the CO2 gas mixture also includes 10% volume fraction of argon. The space velocity of the H2 gas and the CO2 gas for the hydrogenation reaction to produce light olefins is 1000mL / (gcat·h). The temperature of the hydrogenation reaction to produce light olefins is 300°C, and the reaction pressure is 4MPa. The components of the product prepared above are tested, and the results are shown in Table 1.

[0054] Example 4

[0055] (1) Preparation of composite catalyst for hydrogenation to produce light olefins

[0056] Ferric nitrate and copper nitrate are dissolved in water to obtain a mixed solution (the concentration of ferric nitrate in the mixed solution is 0.35 mol / L, and the molar ratio of ferric nitrate to copper nitrate is 1.37:1), which is placed in a water bath heating device with ultrasonic function and heated to 70°C, TiO2 with a particle size of 10 nm is added thereto, and then 1 mol / L sodium carbonate aqueous solution is added thereto for coprecipitation reaction, until the pH of the coprecipitation reaction system is 8, the addition of the precipitant is stopped, and the uniformly mixed system is subjected to static aging, and a coprecipitation reaction is carried out to obtain a mixed slurry, wherein the coprecipitation reaction time is 5 hours and the static aging time is 6 hours. The mixed slurry is separated, and the obtained solid material is dried at 100°C for 24 hours, and then calcined at 400°C for 3 hours to obtain an active precursor FeCu / TiO2. The active precursor is compacted and crushed, and a 20-40 mesh portion is screened out, which is mechanically mixed with a 20-40 mesh SAPO-34 molecular sieve to obtain a composite catalyst for hydrogenation to produce low-carbon olefins. The molar ratio of Fe to Cu in the composite catalyst for hydrogenation to prepare low-carbon olefins is 0.8:1, the ratio of the molar number of added TiO2 to the total molar number of Fe and Cu is 0.10:1. The weight ratio of the active precursor FeCu / TiO2 and SAPO-34 molecular sieve is 2:1.

[0057] (2) Preparation of light olefins

[0058] The above-obtained composite catalyst for preparing light olefins by hydrogenation is placed in a fixed bed reactor, and is subjected to reduction pretreatment in a reducing mixed gas atmosphere consisting of the first gas hydrogen and the second gas nitrogen to obtain an active composite catalyst for preparing light olefins by hydrogenation. The volume ratio of the first gas hydrogen to the second gas argon is 4:1, the reduction temperature is 300°C, the reduction pressure is 0.11MPa, the reduction time is 3h, and the space velocity of the reducing mixed gas consisting of the first gas hydrogen and the second gas argon is 6000mL / (gcat·h).

[0059] The H2 gas and CO2 gas are subjected to a hydrogenation reaction to produce light olefins under the action of an active hydrogenation catalyst. The volume ratio of the H2 gas and the CO2 gas is 3:1, and the mixture of the H2 gas and the CO2 gas also includes 4% nitrogen by volume. The space velocity of the hydrogenation reaction of the H2 gas and the CO2 gas to produce light olefins is 6000mL / (gcat·h). The temperature of the hydrogenation reaction to produce light olefins is 350°C, and the reaction pressure is 3MPa. The components of the product prepared above are tested, and the results are shown in Table 1.

[0060] Example 5

[0061] (1) Preparation of composite catalyst for hydrogenation to produce light olefins

[0062] Ferric nitrate and copper nitrate are dissolved in water to obtain a mixed solution (the concentration of ferric nitrate in the mixed solution is 0.35 mol / L, and the molar ratio of ferric nitrate to copper nitrate is 1.37:1), which is placed in a water bath heating device with ultrasonic function and heated to 70°C, TiO2 with a particle size of 10 nm is added thereto, and then 1 mol / L sodium carbonate aqueous solution is added thereto for coprecipitation reaction, until the pH of the coprecipitation reaction system is 6, the addition of the precipitant is stopped, and the uniformly mixed system is subjected to static aging, and a coprecipitation reaction is carried out to obtain a mixed slurry, wherein the coprecipitation reaction time is 5 hours and the static aging time is 6 hours. The mixed slurry is separated, and the obtained solid material is dried at 100°C for 24 hours, and then calcined at 400°C for 3 hours to obtain an active precursor FeCu / TiO2. The active precursor is compacted and crushed, and a 20-40 mesh portion is screened out, which is mechanically mixed with a 20-40 mesh SAPO-34 molecular sieve catalyst to obtain a composite catalyst for hydrogenation to produce low-carbon olefins. The molar ratio of Fe to Cu in the composite catalyst for hydrogenation to prepare low-carbon olefins is 1.5:1, the ratio of the molar number of added TiO2 to the total molar number of Fe and Cu is 0.20:1. The weight ratio of the active precursor FeCu / TiO2 and SAPO-34 molecular sieve is 2:1.

[0063] (2) Preparation of light olefins

[0064] The above-obtained composite catalyst for preparing light olefins by hydrogenation is placed in a fixed bed reactor, and is subjected to reduction pretreatment in a reducing mixed gas atmosphere consisting of the first gas hydrogen and the second gas nitrogen to obtain an active composite catalyst for preparing light olefins by hydrogenation. The volume ratio of the first gas hydrogen to the second gas argon is 4:1, the reduction temperature is 300°C, the reduction pressure is 0.11MPa, the reduction time is 3h, and the space velocity of the reducing mixed gas consisting of the first gas hydrogen and the second gas argon is 6000mL / (gcat·h).

[0065] The H2 gas and CO2 gas are subjected to a hydrogenation reaction to produce light olefins under the action of an active hydrogenation catalyst. The volume ratio of the H2 gas and the CO2 gas is 3:1, and the mixture of the H2 gas and the CO2 gas also includes 4% nitrogen by volume. The space velocity of the hydrogenation reaction of the H2 gas and the CO2 gas to produce light olefins is 6000mL / (gcat·h). The temperature of the hydrogenation reaction to produce light olefins is 350°C, and the reaction pressure is 3MPa. The components of the product prepared above are tested, and the results are shown in Table 1.

[0066] Example 6

[0067] The difference between Example 6 and Example 1 is that the molar ratio of Fe to Cu in the composite catalyst for hydrogenating light olefins is 1.1:1, and the ratio of the molar number of added TiO2 to the total molar number of Fe and Cu is 0.15:1.

[0068] Example 7

[0069] The difference between Example 7 and Example 1 is that the molar ratio of Fe to Cu in the composite catalyst for hydrogenating light olefins is 1.72:1, and the ratio of the molar number of added TiO2 to the total molar number of Fe and Cu is 0.15:1.

[0070] Example 8

[0071] The difference between Example 8 and Example 1 is that the molar ratio of Fe to Cu in the composite catalyst for hydrogenation to prepare light olefins is 1.37:1, and the ratio of the molar number of added TiO2 to the total molar number of Fe and Cu is 0.08:1.

[0072] Example 9

[0073] The difference between Example 9 and Example 1 is that the molar ratio of Fe to Cu in the composite catalyst for hydrogenation to produce light olefins is 1.37:1, and the ratio of the molar number of added TiO2 to the total molar number of Fe and Cu is 0.2:1.

[0074] Example 10

[0075] The difference between Example 10 and Example 1 is that the precipitant is potassium carbonate.

[0076] Embodiment 11

[0077] The difference between Example 11 and Example 1 is that the temperature of the hydrogenation reaction to produce light olefins is 320°C.

[0078] Example 12

[0079] The difference between Example 12 and Example 1 is that the temperature of the hydrogenation reaction to produce light olefins is 360°C.

[0080] Example 13

[0081] The difference between Example 13 and Example 1 is that the molar ratio of Fe to Cu in the composite catalyst for preparing low-carbon olefins by hydrogenation is 2.2:1, the ratio of the molar number of added TiO2 to the total molar number of Fe and Cu is 0.30:1. The weight ratio of the active precursor FeCu / TiO2 to the SAPO-34 molecular sieve is 0.5:1.

[0082] Comparative Example 1

[0083] Weigh 22.7g of copper nitrate, 11g of zinc nitrate, and 3.5g of aluminum nitrate and dissolve them in 200g of deionized water to prepare a mixed salt solution. Weigh 31g of sodium carbonate and dissolve it in 300g of deionized water to prepare a precipitant solution. Place the mixed salt solution in a three-necked flask, heat the solution temperature to 70°C in a water bath, and then use a peristaltic pump to add the precipitant solution to the flask at a rate of 5mL / min to perform a coprecipitation reaction to obtain a mixed slurry. After the addition is completed, the aging time is 6h. Separate the mixed slurry, dry the obtained solid material at 110°C for 24h, and then calcine it at 400°C for 3h to obtain the active precursor CuZnAl. The active precursor is compacted and crushed, and the 20-40 mesh part is sieved out, which is mechanically mixed with the 20-40 mesh SAPO-34 molecular sieve to obtain a composite catalyst for hydrogenation to produce low-carbon olefins. The weight ratio of the active precursor CuZnAl to the SAPO-34 molecular sieve is 2:1.

[0084] The prepared composite catalyst for preparing low-carbon olefins by hydrogenation is placed in a fixed bed reactor, and is subjected to reduction pretreatment in a reducing mixed gas atmosphere consisting of the first gas hydrogen and the second gas nitrogen to obtain an active composite catalyst for preparing low-carbon olefins by hydrogenation. The volume ratio of the first gas hydrogen to the second gas argon is 4:1, the reduction temperature is 300°C, the reduction pressure is 0.11MPa, the reduction time is 3h, and the space velocity of the reducing mixed gas consisting of the first gas hydrogen and the second gas argon is 6000mL / (gcat·h).

[0085] The H2 gas and CO2 gas are subjected to a hydrogenation reaction to produce light olefins under the action of an active hydrogenation catalyst. The volume ratio of the H2 gas and the CO2 gas is 3:1, and the mixture of the H2 gas and the CO2 gas also includes 4% nitrogen by volume. The space velocity of the hydrogenation reaction of the H2 gas and the CO2 gas to produce light olefins is 6000mL / (gcat·h). The temperature of the hydrogenation reaction to produce light olefins is 350°C, and the reaction pressure is 3MPa. The components of the product prepared above are tested, and the results are shown in Table 1.

[0086] The hydrogenation products of light olefins prepared in the above examples and comparative examples were tested for relevant properties, and the results are shown in Table 1. The test data in the table are explained as follows:

[0087] Calculation method of CO2 conversion rate:

[0088]

[0089] Calculation method of CO selectivity:

[0090]

[0091] Calculation method for hydrocarbon product selectivity:

[0092]

[0093] Among them, in the above formula: X is the conversion rate, S is the selectivity, A is i represents the chromatographic peak area of ​​component i, f i represents the correction factor of component i, wherein the correction factor f used in the present invention is i A standard gas of known concentration is passed into the chromatograph and the peak area is measured. The ratio of the concentration to the peak area is the correction factor.

[0094] Definition of catalyst life: The composite catalyst for hydrogenation to produce light olefins prepared in the examples and comparative examples is used for hydrogenation to produce light olefins. When its selectivity for C2-C4 unsaturated olefins is less than 50%, the catalyst is considered to be deactivated. This period of time is recorded as the catalyst life (h).

[0095] Table 1

[0096]

[0097] Here, the data in the table need to be further explained that since the selectivity of the composite catalyst prepared in Comparative Example 1 for C2-C4 unsaturated olefins is less than 50%, it is represented by " / " in Table 1. In fact, the time for which the selectivity for C2-C4 unsaturated olefins is not less than 30% is 1.3h.

[0098] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:

[0099] Embodiments 1 to 13 are the hydrogenation to produce light olefins reaction using the hydrogenation to produce light olefins composite catalyst provided by the present invention. In the corresponding hydrogenation to produce light olefins reaction, the CO2 conversion rate and the selectivity for C2-C4 unsaturated olefins in the hydrocarbon products are at a good comprehensive level, and the selectivity for C2-C4 unsaturated olefins is above 60%, while the selectivity for CH4, C2-C4 saturated hydrocarbons and C5+ hydrocarbon substances is lower. In particular, the proportion of each component in the hydrogenation to produce light olefins composite catalyst is controlled within a preferred range, and the hydrogenation to produce light olefins reaction effect corresponding to the hydrogenation to produce light olefins composite catalyst is better, and the catalyst also has a good service life.

[0100] Comparative Example 1 is a hydrogenation reaction to produce light olefins using a conventional catalyst. In the corresponding hydrogenation reaction to produce light olefins, although the CO2 conversion rate is acceptable, the selectivity for C2-C4 unsaturated olefins in the hydrocarbon products is far different from that in the embodiments of the present invention, the selectivity for CH4 is in a relatively high range, and the catalytic life of the composite catalyst is poor.

[0101] It can be seen that the use of the composite catalyst for hydrogenation to prepare light olefins provided by the present invention in the hydrogenation to prepare light olefins reaction can not only effectively improve the CO2 conversion rate, but also further improve the selectivity of the reaction for C2-C4 unsaturated olefins. The composite catalyst for hydrogenation to prepare light olefins provided by the present invention is of great significance for achieving more efficient CO2 resource utilization and promoting the green transformation of the chemical industry and economic sustainable development.

[0102] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A composite catalyst for preparing light olefins by hydrogenation, characterized in that: The composite catalyst for hydrogenation to produce low-carbon olefins comprises a first component and a second component, wherein the first component is FeCu / TiO2, the second component is at least one of SAPO-34 molecular sieve, SAPO-18 molecular sieve, ZSM-5 molecular sieve and SSZ-13 molecular sieve, and the Fe in the first component is iron oxide, and the Cu in the first component is copper oxide.

2. The composite catalyst for preparing light olefins by hydrogenation according to claim 1, characterized in that: The weight ratio of the first component to the second component is (1-5):1; Preferably, the molar ratio of the Fe and the Cu in the first component is (0.5-2):1, and the ratio of the molar number of the TiO2 to the total molar number of the Fe and the Cu is (0.01-0.25):1; Further preferably, the molar ratio of the Fe to the Cu in the first component is (0.8-1.5):1, and the ratio of the molar number of the TiO2 to the total molar number of the Fe and the Cu is (0.10-0.20):1; Preferably, the second component is SAPO-34 molecular sieve; Preferably, the particle size of the composite catalyst for hydrogenation to produce light olefins is 10 to 100 meshes.

3. A method for preparing a composite catalyst for hydrogenating light olefins according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: A soluble salt of Fe and a soluble salt of Cu are dissolved in water to obtain a mixed solution, which is heated and TiO2 and a precipitant are sequentially added thereto to perform a coprecipitation reaction to obtain a mixed slurry; Separating the mixed slurry, drying and calcining the obtained solid matter to obtain an active precursor FeCu / TiO2; The active precursor FeCu / TiO2 is mixed with the second component to obtain the composite catalyst for hydrogenation to produce light olefins.

4. The method for preparing the composite catalyst for hydrogenating to prepare light olefins according to claim 3, characterized in that: When the pH of the coprecipitation reaction system is 6 to 9, stop adding the precipitant; Preferably, when the pH of the coprecipitation reaction system is 6 to 8, the addition of the precipitant is stopped; Preferably, the precipitant is an aqueous carbonate solution; Preferably, the carbonate aqueous solution is at least one of a sodium carbonate aqueous solution, a potassium carbonate aqueous solution and an ammonium carbonate aqueous solution; Preferably, the concentration of the precipitant is 0.1 to 1 mol / L; Preferably, the concentration of the soluble salt of Fe in the mixed solution is 0.1 to 1.0 mol / L; Preferably, the concentration of the soluble salt of Cu in the mixed solution is 0.1-0.8 mol / L.

5. The method for preparing the composite catalyst for hydrogenating to prepare light olefins according to claim 3, characterized in that: The temperature of the coprecipitation reaction is 30-90°C; Preferably, the coprecipitation reaction time is 1 to 12 hours; Preferably, after the coprecipitation reaction is completed, the mixed slurry is subjected to static aging to obtain the mixed slurry; preferably, the static aging time is 0.1 to 8 hours.

6. The method for preparing the composite catalyst for hydrogenation to produce light olefins according to any one of claims 3 to 5, characterized in that: The drying temperature is 100-120°C, and the drying time is 2-24h; Preferably, the calcination temperature is 300-600°C, and the calcination time is 2-6h; Preferably, the particle size of the active precursor FeCu / TiO2 is 10 to 100 mesh; Preferably, the particle size of the second component is 20 to 100 mesh; Preferably, the particle size of the TiO2 is 10 to 100 nm.

7. A hydrogenation reaction to produce light olefins, characterized in that: The hydrogenation reaction to produce light olefins uses CO2 as a raw material and the composite catalyst for hydrogenation to produce light olefins described in claim 1 or 2 as a catalyst.

8. A method for preparing light olefins by hydrogenation according to claim 7, characterized in that: The method comprises: The catalyst is subjected to reduction pretreatment in the presence of a reducing gas to obtain an active catalyst for preparing light olefins by hydrogenation; The H2 gas and CO2 gas are subjected to the hydrogenation to produce light olefins reaction under the action of the active hydrogenation to produce light olefins composite catalyst.

9. The method for preparing light olefins by hydrogenation according to claim 8, characterized in that: The reducing gas includes a mixed gas consisting of a first gas and a second gas, wherein the first gas is hydrogen, and the second gas is at least one of nitrogen, argon and helium; Preferably, the space velocity of the mixed gas composed of the first gas and the second gas is 1000 to 20000 mL / (gcat·h); Preferably, the reduction temperature is 200-400° C., the reduction time is 2-5 h, and the reduction pressure is 0.09-0.11 MPa; Preferably, the volume ratio of the first gas to the second gas in the mixed gas is (0.05-19):

1.

10. The method for preparing light olefins by hydrogenation according to claim 8 or 9, characterized in that: The volume ratio of the H2 gas to the CO2 gas is (2-4):1; Preferably, the space velocity of the hydrogenation reaction of the H2 gas and the CO2 gas to produce light olefins is 1000 to 20000 mL / (gcat·h); Preferably, the temperature of the hydrogenation reaction to produce light olefins is 300-400°C, and the reaction pressure is 1-4MPa; Preferably, the H2 gas and CO2 gas mixture further comprises 1 to 10% by volume of at least one of nitrogen, argon and helium as a protective gas.